Predicting Working Memory (Visual-Spatial) Based on Selective Attention and Phonological Awareness in 8-12 Year Old Male Students with Dyslexia in 5th Discrete of Tehran, Iran - Marjan Sadat Momeni; Majid Zargham-Hajebi; Nader Monirpoor (Vesnu Publications, 2020)
Introduction: Working memory (WM) is a limited-capacity processing resource, which includes storing information when processing information. However, children with dyslexia have difficulty remembering this limited amount. Therefore, the purpose of this study is to predict WM based on selective attention and phonological awareness of elementary school children with dyslexia.Materials and Methods: This study was a correlational study in which the samples consisted of 203 male students aged 8-12 years studying at schools in the fifth district of Tehran Metropolitan, Iran, who were selected using multi-stage random sampling method. Dyslexia checklist, Andre Rey's Spatial Visual Memory Test, Stroop test, and Phonological Awareness Survey were applied to collect information. In addition to descriptive statistical methods, simultaneous multiple regression analysis method was used.Results: The results showed that 36.5% of the variance of WM in the selective attention test can be explained, with the highest mean related to the cognitive control level. Moreover, 35.5% of the variance of visual WM can be explained in the phonological awareness test, with the highest average associated with the final phoneme removal. Conclusion: Selective attention and phonological awareness seem to play a significant role in predicting visual-spatial WM in boys with dyslexia.